Great earthquake surface ruptures along backthrust of the Janauri anticline, NW Himalaya. (1st January 2017) - Jayangondaperumal, R.; Kumahara, Y.; Thakur, V.C.; Kumar, Anil; Srivastava, Pradeep; Dubey, Shubhanshu; Joevivek, V.; Dubey, Ashok Kumar
Graphical abstract: Folded scarp warping the gravel bed along the northern flank of Janauri anticline. Highlights: To precisely date earthquake events on the foreland verging thrust (i.e. HFT) in NW Himalaya directly, attempts to develop earthquake chronologies have focused on earthquake ruptures associated with backthrust of the HFT system. Further our study may complements the age constraint for the great/large earthquake event along forethrust and thus better understanding the seismic hazard along densely populated regions of the Himalayan foothills. Abstract: Results of a paleoseismic trenching investigation on a backthrust in the northern margin of Janauri hill, at Mehandpur (31°18′11.37″N, 76°18′31.47″E), Sub-Himalayan range of the Himachal Himalaya are presented. The active backthrust revealed the last event took place after 0.8 ± 0.03 ka ago (i.e. post CE 1200). The age of the last earthquake with a minimum fault slip ∼1 m along F1 fault and presence of single colluvium on the back thrust nearly matches with an earthquake event previously documented on the Bhatpur forethrust of the Himalayan frontal thrust system. Uplifted and truncated fluvial terraces due to displacement on the backthrust are preserved along several north flowing river valley sections in the northern limb of Janauri anticline. The long-term vertical uplift rate calculated through dividing difference between current elevation and elevation of current river grade is 1.08 ± 0.08 mm/yr. Field evidence shows fore and backthrusts are active and they form simultaneously, but displacements are episodic suggesting the backthrust develops either due to locking of forethrust or to accommodate a large amount of fault slip due to magnitude of earthquake event along the forethrust. Further, the backthrust may be used as an indirect method of inferring the age of the last event that took place along the forethrust.